REDDIT’S COMMUNITIES & CONSEQUENCES - Halavais, Alexander; Massanari, Adrienne; Bergstrom, Kelly; Poor, Nathaniel (AoIR Selected Papers of Internet Research, 2020)
As a platform, Reddit provides a bit of a conundrum. Despite being visited by more people than Netflix and remaining one of the most visited spaces on the web, it remains extraordinarily resistant to generalization. Some of the worst of Internet culture can be found on the site. It has served to amplify the voices of misogynists, supported vigilantism, and hosted child pornography. At the same time, some of the more civil conversations and learning communities appear on the site, with subreddits like Change My View fostering respectful deliberation. Even more than many other platforms, the lack of centralized moderation means that Reddit contains a very wide range of practices, some of them quite extreme. But because these exist on a single platform, users bring these practices with them, both to the “front page” of the platform, and to other areas within. The three papers that make up this panel seek to better understand localized behaviors and how they may relate to global flows of participants and practices. Of course, many of the discursive patterns that were fostered in subreddits make their way into other online and offline contexts. But before they do that, they have often been produced as part of a culture local to one subreddit, or to a “neighborhood” of subreddits. How these practices emerge, evolve, and relate to the actions of their users runs as a thread through the three presentations.